ANALISIS PENGARUH PEMBIAYAAN MODAL KERJA, PEMBIAYAAN INVESTASI, DAN PEMBIAYAAN KONSUMTIF TERHADAP TOTAL ASET BANK ACEH PERIODE 2016-2019 - Israk Ahmadsyah; Rahmati Rahmati; Safarul Aufa (Jurnal Ekonomi Regional Unimal, 2019)
The study aims to analyze the influence of working capital financing, investment financing, and consumer financing, against the total asset of PT Bank Aceh Syariah. The study uses a quantitative research method, and as a secondary data, utilizes the time-series data. The data collection occurred from September 2016 to March 2019. The hypothesis testing uses multiple linear regression analysis method with the assistance of Statistical Package for The Social Science (SPSS) 22. The partial analysis results (t-test) suggests that the working capital and investment financing did not affect Bank Aceh’s total asset. The simultaneous result analysis (F-test) shows that every independent variable collectively gives impact on the Bank Aceh Syariah’s total asset during September 2016 to March 2019 period.